Multiple halal logos and Malays’ beliefs: a case of mixed signals - Aziz , Shafiq; Haque, A. K. M. Ahasanul; A, Omar (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
The halal logo(s) issued by JAKIM tend to confuse consumers as they greatly lacked information about the genuine halal logo. This was found by conducting open ended, but structured interviews from 20 Malays and showing them 10 halal logos (9 original and 1 fake) to see whether they could recognize the fake from the originals. This research found that while all the respondents had difficulty in differentiating the real halal logo from the fake, they all preferred a single, unified halal logo to end the confusion. This finding holds serious implications for JAKIM: it needs to extend efforts to educate people about the in-practice halal logo, without which many people would remain in the same confusion. This bears particular importance for the religious food requirements of Muslims as genuine halal logo determines the permissibility of food being taken.